Optimization Scientific Journal Publications For Teachers SMA Negeri 1 Kendal - Sehabuddin, Ahmad; Lola Kurnia Pitaloka (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2020)
Scientific publications are part of the research cycle that researchers must carry out when they have finished carrying out their research. The priority problem faced by SMA Negeri 1 Kendal teachers is that the teachers do not understand scientific journal publication techniques comprehensively. The target in this service is SMA Negeri 1 Kendal teachers. The solution offered to overcome this problem is to provide training for scientific journal publication for high school teachers Negeri 1 Kendal. The aim of holding scientific journal publication training is to increase the understanding of teachers related to scientific journal publication techniques; provide knowledge about scientific journal publication sites, both accredited and non-accredited journals; and facilitate teachers in publishing scientific journals. Community service activities regarding the optimization of scientific journal publications for SMA Negeri 1 Kendal teachers have a positive impact in terms of increasing understanding of scientific publication techniques and being able to practice scientific publication procedures in scientific journals. This service can help and improve the quality and quantity of scientific article publications in scientific journals for SMA Negeri 1 Kendal teachers.